Aggressor-victim dissent in perceived legitimacy of aggression in soccer: The moderating role of situational background - Rascle, O.; Traclet, A.; Souchon, N.; Coulomb-Cabagno, G.; Petrucci, C. (Research Quarterly for Exercise and Sport, 2010)
The purpose of this study was to investigate the aggressor-victim difference in perceived legitimacy of aggression in soccer as a function of score information (tied, favorable, unfavorable), sporting penalization (no risk, yellow card, red card), and type of aggression (instrumental, hostile). French male soccer players (N = 133) read written scenarios and rated the legitimacy of the described aggressive act depending on a specific perspective (aggressor or victim) and situational information. A significant aggressor-victim difference in perception of instrumental aggression was found in situations where the score was tied or where there was no risk to be caught. In addition, aggressors were affected by such information, whereas victims were not. The discussion focuses on explanations and implications of such divergences in aggressive sport situations.